2000
DOI: 10.1016/s0006-3495(00)76489-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Resonance Studies of Agonist/Antagonist Binding to theHuman δ-Opioid Receptor: New Structural Insights into Receptor-Ligand Interactions

Abstract: Structural changes accompanying the binding of ligands to the cloned human delta-opioid receptor immobilized in a solid-supported lipid bilayer have been investigated using coupled plasmon-waveguide resonance spectroscopy. This highly sensitive technique directly monitors mass density, conformation, and molecular orientation changes occurring in anisotropic thin films and allows direct determination of binding constants. Although both agonist binding and antagonist binding to the receptor cause increases in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
105
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 30 publications
20
105
1
Order By: Relevance
“…We have observed the same slow rate of agonist-induced conformational change with a different f luorescent reporter on Cys-125 in TM3 and on Cys-285 in TM6 of the ␤ 2 AR (Fig. 1 A) (23), and Salamon et al observed a similar rate of agonistinduced conformational changes in the ␦-opioid receptor analyzed by surface plasmon resonance spectroscopy (24). Thus, agonist binding precedes the conformational change.…”
Section: The Effect Of Full and Partial Agonists On The Fluorescence supporting
confidence: 69%
“…We have observed the same slow rate of agonist-induced conformational change with a different f luorescent reporter on Cys-125 in TM3 and on Cys-285 in TM6 of the ␤ 2 AR (Fig. 1 A) (23), and Salamon et al observed a similar rate of agonistinduced conformational changes in the ␦-opioid receptor analyzed by surface plasmon resonance spectroscopy (24). Thus, agonist binding precedes the conformational change.…”
Section: The Effect Of Full and Partial Agonists On The Fluorescence supporting
confidence: 69%
“…Unexpectedly, the interaction resulted in a negative curve. The generation of negative curves has previously been linked to a ligand-induced structural change; for example, the immobilized component may undergo a decrease of its hydrodynamic radius (29,30). It is plausible that the negative curve obtained here is due to a heparin-induced conformational change of the lipoprotein.…”
Section: Hs/heparinmentioning
confidence: 60%
“…Negative signals can be observed when the immobilized ligand undergoes a conformational change, often related to an analyte-induced decrease of its hydrodynamic radius. This change in conformation results in a decrease of the refractive index (29,30). Thus, the negative signals observed for HS/heparin interaction with HDL-SAA likely correspond to a conformational change of the lipoprotein.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, they repulse if they present a different mismatch sign [101]. For instance, the activation of a receptor after ligand binding can change its hydrophobic thickness [102] and consequently the interaction potential with neighbouring proteins.…”
Section: Appendix 2 Nature Of Protein-protein Interactionsmentioning
confidence: 99%